DIGITAL MARKETING TO DRIVE ADOPTION OF DIGITAL PAYMENTS IN THE MODERN ERA - Elona Sitohang; Yolanda Masnita; Kurniawati Kurniawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The development of information and communication technology has driven the adoption of digital payments around the world. Similarly, Payment methods have evolved considerably, shifting from conventional cash transactions to modern digital payment systems. This not only simplifies the transaction process but also increases security and efficiency in transactions. In the context of digital payment adoption, digital marketing that increases awareness can influence positive attitudes towards using digital payments, as well as provide relevant information to reduce concerns and increase trust. This research seeks to explore the impact of user-friendliness, usefulness with digital marketing mediation, social influence, and credibility affects digital payment adoption. The results of data analysis testing conducted using SEM (Structural Equation Model), namely AMOS with 230 respondents, show that the four hypotheses proposed are supported. These results can contribute to industries that implement digital payments such as banks and e-commerce to encourage the adoption of digital technology.